Quantification of cortisol in human eccrine sweat by liquid chromatography – tandem mass spectrometry. Issue 6 (9th February 2016) - Jia, Min; Chew, Wade M.; Feinstein, Yelena; Skeath, Perry; Sternberg, Esther M.
Abstract : Cortisol was separated from its isomers and quantified by HPLC-MS/MS in human eccrine sweat samples. Abstract : Cortisol has long been recognized as the "stress biomarker" in evaluating stress related disorders. Plasma, urine or saliva are the current source for cortisol analysis. The sampling of these biofluids is either invasive or has reliability problems that could lead to inaccurate results. Sweat has drawn increasing attention as a promising source for non-invasive stress analysis. A sensitive HPLC-MS/MS method was developed for the quantitation of cortisol ((11β)-11, 17, 21-trihydroxypregn-4-ene-3, 20-dione) in human eccrine sweat. At least one unknown isomer that has previously not been reported and could potentially interfere with quantification was separated from cortisol with mixed mode RP HPLC. Detection of cortisol was carried out using atmospheric pressure chemical ionization (APCI) and selected reaction monitoring (SRM) in positive ion mode, using cortisol-9, 11, 12, 12-D4 as internal standard. LOD and LOQ were estimated to be 0.04 ng ml −1 and 0.1 ng ml −1, respectively. Linear range of 0.10–25.00 ng ml −1 was obtained. Intraday precision (2.5%–9.7%) and accuracy (0.5%–2.1%), interday precision (12.3%–18.7%) and accuracy (7.1%–15.1%) were achieved. This method has been successfully applied to the cortisol analysis of human eccrine sweat samples. This is the first demonstration that HPLC-MS/MS can be used for the sensitive and highly specific determination of cortisol in human eccrine sweat in the presence of at least one isomer that has similar hydrophobicity as cortisol. This study demonstrated that human eccrine sweat could be used as a promising source for non-invasive assessment of stress biomarkers such as cortisol and other steroid hormones.